2002
DOI: 10.1021/jp021539h
|View full text |Cite
|
Sign up to set email alerts
|

Solvation and Ionization Stages of HCl on Ice Nanocrystals

Abstract: The study focuses on acid adsorption on cold ice particle surfaces. The investigation encompasses HCl, DCl, and HBr adsorbate spectroscopy, Monte Carlo simulations of molecular HCl adsorbate on a model ice particle, and ab initio studies of HCl solvation and ionization in mixed acid−water clusters. It is shown that ice nanocrystal surfaces offer a range of adsorption sites, in which HCl freezes in different recognizable solvation stages. These stages were identified spectroscopically and assigned, with the hel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

26
271
3
2

Year Published

2005
2005
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 127 publications
(302 citation statements)
references
References 95 publications
26
271
3
2
Order By: Relevance
“…To date, TP-TOF-SIMS has revealed that both HCl and NH 3 molecules adsorbed on pure ASW films are hydrated considerably up to 140 K [22][23][24], which is consistent with the conclusions drawn using different approaches [3][4][5][6]8,9,13,14]. However, very little is known about intermolecular interactions at the surface of acidic and basic water-ice films including hydrated HCl or NH 3 molecules, respectively.…”
Section: Discussionsupporting
confidence: 73%
See 1 more Smart Citation
“…To date, TP-TOF-SIMS has revealed that both HCl and NH 3 molecules adsorbed on pure ASW films are hydrated considerably up to 140 K [22][23][24], which is consistent with the conclusions drawn using different approaches [3][4][5][6]8,9,13,14]. However, very little is known about intermolecular interactions at the surface of acidic and basic water-ice films including hydrated HCl or NH 3 molecules, respectively.…”
Section: Discussionsupporting
confidence: 73%
“…Molina et al [1] proposed that the reaction rate between HCl and ClNO 2 is enhanced considerably by the existence of ice particles, but detailed reaction pathways for the ionization and solvation of HCl adsorbed on a water-ice surface are not yet fully understood. So far, a number of groups have been extensively tackling these fascinating topics by infrared spectroscopy (IR) [3][4][5][6][7][8][9], reactive Cs + ion scattering (RIS) [10,11], near edge X-ray absorption fine structure (NEXAFS) [12], and temperature-programmed desorption (TPD) [8,9,13,14] analyses, and computer simulations [3,5,[15][16][17][18][19][20][21]. Recently, arguments tend to converge on the conclusion that both the ionization and solvation of HCl molecules occur as proposed by Devlin and coworkers [3][4][5].…”
Section: Introductionmentioning
confidence: 99%
“…The most extensively studied example of ice surface reaction is the ionization of strong protic acids such as HCl, for which reviews are available. 68 The author's group has examined the adsorption and ionization of HCl on ice films at low temperatures (50 -140 K) with RIS and LES. 12,34 Figure 11(a) shows the RIS spectrum obtained from a D 2 O-ice film surface with HCl adsorbates (~0.3 ML) at a temperature of 70 K. A family of Cs(D 2 O) n + (n = 1 -4) peaks appear in the spectrum, along with a CsHCl + peak.…”
Section: Reactive Ion Scattering Of Lowmentioning
confidence: 99%
“…It is now generally admitted that the ice surface plays also a crucial role in the activation of chemical reactions leading to ozone destroying species production [3]. In this context, there has been a widespread interest for the interaction of HCl with ice [4][5][6][7][8][9][10][11]. Despite the large number of experimental and theoretical studies devoted to this system, the influence of the UV radiation on the adsorbed molecule has not been extensively characterized yet [4,12].…”
Section: Introductionmentioning
confidence: 99%
“…It has been actually suggested that the ice uppermost layer is liquidlike at 190 K [13,15]. Most of the published experiments suggest a thermal activated HCl ionization [5,16]. From a theoretical point of view, calculations predict a dissociation mechanism that depends strongly either on the arrangement of the dangling bonds [7,17,18] or on defective sites on the surface [19,20] or on the possibility for HCl to be inserted in the uppermost layer [9,10].…”
Section: Introductionmentioning
confidence: 99%